THE USE OF SYMBOLIC CONVERGENCE IN K-POP ALBUM MARKETING (MARKETING OF ‘ISTJ’ ALBUM AMONG NCTZEN) - Ramadhani, Amelia; Utari, Prahastiwi; Hartjarjo, Sri (Departemen Ilmu Komunikasi Universitas Andalas, 2024)
There are many methods used in product marketing in the current digital communication era. One of them is by joining groups or online communities that are relevant to the product to be offered through active participation, making contributions, and building the reputation of the intended group. Effective marketing in this era can be done through symbolic convergence. The use of language in marketing that is creative, imaginative, and at the same time evocative and binds the intended community together. This article describes and analyzes how marketing on NCT Dream's 'ISTJ' album is associated with Symbolic Convergence Theory. This research method is conducted qualitatively. First, analyze the content of marketing messages in digital media used in this case through Instagram social media, then continue by looking at NCTzen comments on the messages conveyed. The research results show that the fantasy theme, which contains creative messages with the ability to dramatize in album marketing, has caused a fantasy chain reaction among the NCT Dream fan community. The power of a message containing a fantasy theme will strengthen the unity and cohesiveness of NCT Dream fans, called NCTzens, as well as being a way of digital products marketing in their latest album launch.